2021
DOI: 10.1016/j.amsu.2021.01.094
|View full text |Cite
|
Sign up to set email alerts
|

Trans-cutaneous electrical nerve stimulation to treat dry mouth (xerostomia) following radiotherapy for head and neck cancer. A systematic review

Abstract: Background A dry mouth or xerostomia is one of the most common long-term complications following radiotherapy for head and neck cancer and has a negative impact on quality of life in cancer survivors. Transcutaneous electrical nerve stimulation (TENS) is a novel approach to improving saliva flow in these patients. Objective To perform a systematic review of studies evaluating TENS in the treatment of radiotherapy induced xerostomia in head and neck cancer patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 27 publications
1
10
0
3
Order By: Relevance
“…Clinical trials of transcutaneous electrical nerve stimulation devices and intra-oral electrostimulators have reported increased saliva secretion and possible reductions in dry mouth symptoms, although the evidence is limited by differences and inconsistencies in terms of the duration and type of electrical stimulation used, as well as the study design. 653 No serious adverse events have been reported with the use of available salivary neuro-electrostimulating devices.…”
Section: Radiotherapy-induced Xerostomiamentioning
confidence: 99%
“…Clinical trials of transcutaneous electrical nerve stimulation devices and intra-oral electrostimulators have reported increased saliva secretion and possible reductions in dry mouth symptoms, although the evidence is limited by differences and inconsistencies in terms of the duration and type of electrical stimulation used, as well as the study design. 653 No serious adverse events have been reported with the use of available salivary neuro-electrostimulating devices.…”
Section: Radiotherapy-induced Xerostomiamentioning
confidence: 99%
“…Cuando la capacidad secretora residual de las glándulas salivales aún está presente, puede ser apropiada la estimulación de la secreción salival 46 . Entre las opciones reportadas en la literatura están los fármacos parasimpaticomiméticos, la acupuntura, la fitoterapia, la estimulación nerviosa y la PBMT 38,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] .…”
Section: Manejo Terapéutico Para La Xerostomíaunclassified
“…La estimulación nerviosa eléctrica transcutánea (TENS, por sus siglas en inglés) es una técnica no invasiva que transmite corrientes eléctricas sobre la superficie intacta de la piel con el fin de activar los nervios subyacentes. Se ha propuesto como terapia prometedora para la xerostomía ya que logra estimular la función salival 53 . Existen dos tipos de TENS: la TENS convencional que consiste en la estimulación local de las glándulas salivales y la TENS similar a la acupuntura que consiste en la estimulación a distancia 53,54 .…”
Section: Manejo Terapéutico Para La Xerostomíaunclassified
See 1 more Smart Citation
“…Though these studies have revealed some positive effects, the evidence is insufficient. The instruments need to be refined in shape and material to provide the appropriate electrical impulse to activate the nerves [ 122 , 123 ].…”
Section: Treatmentmentioning
confidence: 99%